Effect of Soil Amendments on Tomato Yield and Soil Characteristic in Acidic Soil at Moulvibazar - Shaheenuzzamn, M; Alam, M S; Miah, M A M; Rasheduzzaman, M; Hossain, M H; Sinthi, F (Bangladesh Agronomy Journal, 2025)
Different soil amendments have various effects on crop growth, yield, and soil properties. The experiment was followed a Randomized Complete Block Design (RCBD) with three replications. Data on tomato growth and yield were collected, and soil samples were analyzed before and after the cropping seasons. Results showed that all amendments significantly increased tomato growth and yield compared to the control (no soil amendments). However, the amendments did not significantly affect days to first flowering (DFF), fruit length (FL), fruit diameter (FD), average fruit weight (AFW), fresh weight per plant (FWPP), or dry matter per plant (DMPP). In contrast, days after 50% flowering (D50 %F), plant height (PH), number of branches per plant, number of fruits per plant (NFPP), number of fruits per plot (NFPP), and yield per hectare (YPH) were significantly influenced by the soil amendments. Additionally, the shelf life of tomatoes was significantly (p > 0.001) affected by the amendments on acidic soil. Regarding soil properties, lime, phosphorus, and Trichoderma improved soil chemical properties. The findings confirm that applying soil amendments enhances tomato growth, yield, and quality. Bangladesh Agron. J. 2024, 27(1): 48-54